The Development of Web-Based Halal Information Systems to Increase Community Satisfaction: A Case Study of Participatory Ergonomics Approach in LPPOM MUI Banten - Wahyu Susihono; Tanty Yuanita; Nurtanto Nurtanto; Irhamni Irhamni (IJECA (International Journal of Education and Curriculum Application), 2018)
One of the services of LPPOM MUI Banten to the community is to provide information through the website, through which the community can independently access various information related to halal certification. In order to achieve optimum service, the website itself should meet the needs of the community, and it should be communicative and informative. This research aims to develop the information system of halal service based on user requirement through ergonomics participatory approach and also to design website by considering ergonomic display. The method used was one group pretest-posttest design, while the sampling was performed using systemic random sampling approach (n = 45). Result shows that the information system of halal service available on the website needs to be developed using ergonomic participatory approach. The development of Halal Information System using participatory ergonomics approach is able to increase user satisfaction by 19.27% (pretest average 23.82 ± 2.81 and post-test 69.73 ± 3.1). The formula development is also discussed.